English Teachers’ Perceptions of School Readiness in Using Merdeka Curriculum - Yunus, Bs. Rifki Patryanto; Muliati, A.; Ariyani, Amra (Journal of Excellence in English Language Education, 2024)
This research aims to find out English teachers’ perceptions of school readiness in using the Merdeka Curriculum. The subject of this research was two English teachers of SMAN 3 Makassar. This research used a descriptive qualitative method. An interview was used as the main instrument to collect the data. The results of this research showed that the two English teachers of SMAN 3 Makassar perceived that SMAN 3 Makassar is ready to use the Merdeka Curriculum due to: (1) SMAN 3 Makassar teachers already have a good understanding of the Merdeka curriculum., (2) the human resources strengthening of SMAN 3 Makassar teachers, and (3) the facilities/infrastructure at SMAN 3 Makassar to be used to fulfill their duty to strengthening students’ competence and developing character under the values of Pancasila. Moreover, the two English teachers tend to view the Merdeka Curriculum as what is needed for students in Indonesia due to its policies to make the students fulfill the Profil Pelajar Pancasila Project (P5), which are: (1) devoted to the Almighty God and possess noble character, (2) independent, (3) cooperative, (4) internationally diverse, (5) critical thinking, and (6) creative. Besides, the students can also choose the subjects that correspond with their interests.